Pengaruh Pemasaran Digital dan Fasilitas Terhadap Keputusan Berkunjung di Desa Wisata Lamajang Kabupaten Bandung - Asti Karini, Rieke Sri Rizki; Isnaeni, Muhammad Nu’man; Sukriadi, Erie Hidayat (Manajemen dan Pariwisata, 2025)
This research was conducted in Lamajang Tourism Village, Bandung Regency, this study aims to determine the influence of digital marketing (X1) and facilities (X2) on the decision to visit (Y) in Lamajang Tourism Village. The method used in this study is a quantitative method with descriptive and verifiative analysis, by distributing questionnaires to 100 tourists to prove the hypothesis that has been made. The results of instrument testing show that all statements are declared valid with results above 0.300 and reliable with results above 0.700. From this study shows that there is a relationship between digital marketing (X1) and facilities (X2) on visiting decisions (Y) with an influence of 58.8% and the remaining 41.2% is a factor that has not been studied. Other test results also show a significant influence between digital marketing variables (X1) and facilities (X2) on visiting decisions (Y) of 0.000 < 0.05, meaning that digital marketing (X1) and facilities (X2) have a strong and significant influence on visiting decisions (Y) both partially and simultaneously. This proves that digital marketing factors and facility factors are factors that influence the decision to visit, but there are some things that must be improved and always updated such as tourist attraction and service quality.